Odpowiedź :
Cześć!
Obliczenia
[tex]3\frac{1}{4}+2\frac{2}{5}-(4\frac{1}{3}-2\frac{2}{3})=3\frac{1\cdot5}{4\cdot5}+2\frac{2\cdot4}{5\cdot4}-(3\frac{3+1}{3}-2\frac{2}{3})=\\\\=3\frac{5}{20}+2\frac{8}{20}-(3\frac{4}{3}-2\frac{2}{3})=5\frac{13}{20}-1\frac{2}{3}=5\frac{13\cdot3}{20\cdot3}-1\frac{2\cdot20}{3\cdot20}=\\\\=5\frac{39}{60}-1\frac{40}{60}=4\frac{39+60}{60}-1\frac{40}{60}=4\frac{99}{60}-1\frac{40}{60}=3\frac{59}{60}[/tex]
Odpowiedź:
3 i 1/4 + 2 i 2/5 - (4 i 1/3 - 2 i 2/3) = 3 i 1/4 + 2 i 2/5 - (3 i 4/3 - 2 i 2/3) = 3 i 5/20 + 2 i 8/20 - 1 i 2/3 = 5 i 13/20 - 1 i 2/3 = 5 i 39/60 - 1 i 40/60 = 4 i 99/60 - 1 i 40/60 = 3 i 59/60